1995
DOI: 10.1165/ajrcmb.13.2.7626287
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane-bound and lysosomal peptidases in human alveolar macrophages.

Abstract: Alveolar macrophages protect the lungs against noxious agents. Proteases and peptidases are essential for this defense and many metabolic activities. Human alveolar macrophages were evaluated for the presence of six important peptidases. Deamidase, a serine peptidase identical with the lysosomal protective protein and possibly with cathepsin A, had high specific activity in alveolar macrophages and is also present in cultured mouse J774A.1 and human U937 cells, used for the sake of comparison. In fractionated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 53 publications
1
37
0
Order By: Relevance
“…An important function of CatA in this multienzyme complex is to protect both glycosidases from rapid proteolysis in the lysosomes (10,33,34,52). Further studies revealed that CatA is a multifunctional enzyme possessing deaminase and esterase activities at neutral pH and carboxypeptidase activity at pH 5.0 to 5.5 (18)(19)(20)(21)50). Peptide substrates with hydrophobic amino acid residues in the P1Ј position are cleaved with high efficiency; however, CatA also shows high affinity for charged residues in this position (13,35,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…An important function of CatA in this multienzyme complex is to protect both glycosidases from rapid proteolysis in the lysosomes (10,33,34,52). Further studies revealed that CatA is a multifunctional enzyme possessing deaminase and esterase activities at neutral pH and carboxypeptidase activity at pH 5.0 to 5.5 (18)(19)(20)(21)50). Peptide substrates with hydrophobic amino acid residues in the P1Ј position are cleaved with high efficiency; however, CatA also shows high affinity for charged residues in this position (13,35,37,38).…”
Section: Discussionmentioning
confidence: 99%
“…38 We purified the enzyme first from human platelets and found it highly concentrated in macrophages and endothelial cells. 19,27,36 Besides Ang I and BK, CATA cleaves endothelin fastest below neutrality. 36 Because it breaks a C-terminal amide bond at neutral pH, we called it deamidase.…”
Section: Discussionmentioning
confidence: 99%
“…The DNA of the expression vector DA-pVL1392 was cotransfected into High Five cells (Invitrogen) with linearized BaculoGold baculovirus DNA. Eighty percent of rCATA proenzyme was secreted, 22,24 then activated with trypsin, measured with Dansyl-Phe-LeuArg, 20,27 and purified on S-Sepharose column.…”
Section: Recombinant Catamentioning
confidence: 99%
See 1 more Smart Citation
“…Wallingford and associates described that Prcp-null mice had elevated levels of alpha-MSH1-13 in the hypothalamus and were leaner and shorter than the wild-type controls on a regular chow diet. Prcp null mice were also resistant to high-fat diet-induced obesity Soisson and associates described the crystal structure of human PRCP E112D polymorphism in the prolylcarboxypeptidase gene was found to be associated with blood pressure response to benazepril in Chinese hypertensive patients Javerzat and associates described overexpression of PRCP during the intermediate phase of the chick chorio-allantoic membrane Recombinant PRCP (rPRCP) metabolized BK1-8 to BK1-7, whereas rPRCP was ineffective in metabolizing BK 1-9 PRCP was found to be active in human cerebrospinal fluid Overexpression of angiotensin type 2 (AT2) receptor in mouse coronary artery endothelial cells was found to increase expression of PRCP, which may contribute to kinin release PRCP is a 4OHTAM resistance factor in estrogen receptor-positive breast cancer cells PRCP gt/gt mice were found to be hypertensive and prothrombotic (Sorrells and Erdos, 1971) (Odya et al, 1978) (Skidgel et al, 1981) (Deddish et al, 1990) (Tan et al, 1993) (Tamaoki et al, 1994) (Suzawa et al, 1995) (Suga et al, 1995) (Jackman et al, 1995) (Watson, Jr. et al, 1997) To deal with proper delivery of blood to the tissues as well as many types of insults, including chemical and physical damage as well as infection, the cardiovascular system has evolved an intricate multilayer of specialized biochemical pathways. Multiple feedback mechanisms controlling blood flow with contrasting effects regulate normal vascular function, which have either stimulatory or inhibitory effects.…”
Section: Cardiovascular System Functionmentioning
confidence: 99%